Identification of termite Coptotermes species collected from Linh Quang pagoda, Ha Dong, Hanoi based on DNA sequences of the fragments in the mitochondrial 16s rRNA gene - Thao, Nguyen Thi; Khoa, Dao Trong; Giang, Le Quang; Huyen, Do Thi; Trung, Nguyen Thi; Thu Hien, Nguyen Thi; Huy, Nguyen Quoc; Hai, Truong Nam (Academia Journal of Biology, 2014)
In 2004, Szalanski et al. developed PCR method based on 2 pairs of specific primers to amplify 2 DNA fragments of 428 bps and 151 bps located in the mitochondrial 16S rRNA for identifying C. formosanus from other Coptotermes species. According to the study, a Coptotermes species is C. formosanus if PCR products were composed of two DNA fragments of 428 bps and 151 bps observed in agarose gel. In this study, using the primers, 2 DNA fragments of 248 bps and 160 bps were amplified from genome of Coptotermes HN1 collected from Ling Quang pagoda. In agarose gel, these DNA fragments looked the same sizes with the DNA amplified from genome of C. formosanus by Szalanski et al. (2004). However, multialigment showed that the sequences were most homologous with the sequences of C. gestroi. Phylogenetic trees were built, based on 40 homologous genes (for each DNA fragment) in GenBank. Coptotermes HN1 belonged to C. gestroi branch, and was far to the branch of C. formosanus in the phylogenetic tree. So the Coptotermes HN1 collected from Linh Quang pagoda, Ha Dong, Hanoi was designated as C. gestroi HN1. From this study, the identification of C. formosanus by PCR developed by Szalanski et al. should have more consideration.